Antibacterial mechanism of hops β-acids against methicillin-resistant Staphylococcus aureus and promote wound healing - Li, Shuanghe; Wei, Shijie; Zhang, Feiyan; Luo, Qi; Yang, Nan; Zhang, Xiao; Liu, Jiayue; Qiao, Xia; Tian, Bingren (Frontiers in Microbiology, 2025)
IntroductionSkin wounds infected by Methicillin-resistant staphylococcus aureus (MRSA) still remain an important clinical challenge. β-acids, secondary metabolites extracted from hops, exhibit a powerful antibacterial effect on MRSA.MethodsIn this study, the antimicrobial activity of β-acids against MRSA and the corresponding mechanism were studied.ResultsThe antimicrobial activity results revealed that β-acids was sensitive to MRSA (MIC = 62.5 μg/mL and MBC = 250 μg/mL). After β-acids treatment, the morphological changes of MRSA, including surface roughness, cellular crumpling, and fracture. The content of extracellular macromolecules, such as nucleic acids and proteins, increased significantly when β-acids treatment was applied, indicating that the integrity and permeability of cell membranes were disrupted. Meanwhile, laser confocal microscopy results showed that the cell membrane was severely damaged. Additionally, β-acids minimized intracellular adenosine triphosphate (ATP), suppressed Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities, and accelerated intracellular reactive oxygen species (ROS) accumulation, ultimately inducing bacterial death. The result of transcriptome RNA sequencing suggested that the pathways involved “carbohydrate metabolism”, “amino acid metabolism”, “energy metabolism”, and “translation”, were significantly enriched. After the mice were successfully modeled with MRSA-infected wounds, β-acids was administered for 15 days, and faster healing of the wound area was observed in the treated group. H&E staining demonstrated gradual regeneration of dermal and epidermal tissues after β-acids treatment. Immunofluorescence results demonstrated that β-acids accelerated wound healing by markedly reducing IL-6 and TNF-α, increasing VEGF levels, and suppressing infection.DiscussionOverall, β-acids may be promising agents for the effective treatment of MRSA.